The Effect of Work Environment and Individual Characteristics on Employee Productivity - Maryani, M.; Gazali, Agus Umar (Golden Ratio of Human Resource Management, 2024)
This study investigates the impact of the work environment and individual characteristics on employee productivity at PT. Bumi Sarana Beton Kalla. The hypothesis posits that both factors significantly influence work productivity. Utilizing a quantitative approach, the research surveyed all 138 company employees in Makassar, with a sample size of 58 respondents determined via the Slovin formula. Primary data were gathered through questionnaires addressing demographic information and responses to measured variables: work environment and individual characteristics. Data analysis involved multiple linear regression, partial t-tests, F-tests, and determination coefficients (R²). The findings reveal that the work environment and individual characteristics positively and significantly affect employee productivity. The regression analysis shows positive coefficients for both variables, indicating that improvements in these factors correlate with increased productivity. These results align with previous studies highlighting the importance of environmental and individual factors in driving work productivity. The implications of this study suggest that companies should focus on creating supportive work environments and fostering the development of individual employee characteristics to enhance productivity. Further research is recommended to validate these findings across different industries and locations and explore technology's role in the work environment.